Prospect of Development Agribusiness Creativity and Innovation - Feby Musti Ariska (Jurnal Peternakan (Jurnal of Animal Science), 2020)
The massive influence of globalization raises demands in many ways, including agriculture. This widespread aspect in Indonesia, which is touted as an agrarian country, is related to the production, distribution and processing of agricultural products. The combination of entrepreneurship that manages agriculture is expected to be able to bring Indonesia to become a more developed country and able to rise from adversity. Previously agriculture was only interpreted in a narrow scope. Now that perspective has changed where previously agriculture only produced primary production of plants and plants, but now agriculture also has the potential as a business. A new perspective opens the horizon of natural resource potential as a path of economic growth that is in line with industrialization in the agricultural sector (agro-industrialization). Creativity and innovation in agribusiness is a must so that the products produced always have a place in the eyes of consumers and provide optimal added value for the actors involved in it.